1967
DOI: 10.1038/bjc.1967.26
|View full text |Cite
|
Sign up to set email alerts
|

Variation of acid-soluble sulphydryl groups during liver regeneration.

Abstract: THE role of acid-soluble -SH compounds in mitosis has been a subject of interest since the work of Rapkine (1931) showed that the "glutathione" content of sea-urchin eggs increased markedly upon fertilisation and underwent cyclic variation during mitosis. Subsequent work by Sakai and Dan (1959) showed that the thiol compound involved was not glutathione but a small polypeptide. The consequences and interpretations of these results have been extensively discussed by Mazia (1959, 1961). Swann (1957Swann ( , 1958… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1968
1968
1983
1983

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The increase noted in the sulfhydryl level of soluble liver proteins following partial hepatectomy is in agreement with the data of Hopsu and Harkonen (1960) who showed by histochemical methods that there is an overall increase in the actual number of sulfhydryl groups in total liver protein during regeneration, and with the findings of Fraser and Cater (1967) that the level of acid-soluble -SH during liver regeneration in the rat increases above normal by 12 hours after hepatectomy and remains elevated until after the first wave of mitosis at 28-30 hours.…”
Section: Intraperitoneal Injection Of 20-methylcholanthrenesupporting
confidence: 92%
“…The increase noted in the sulfhydryl level of soluble liver proteins following partial hepatectomy is in agreement with the data of Hopsu and Harkonen (1960) who showed by histochemical methods that there is an overall increase in the actual number of sulfhydryl groups in total liver protein during regeneration, and with the findings of Fraser and Cater (1967) that the level of acid-soluble -SH during liver regeneration in the rat increases above normal by 12 hours after hepatectomy and remains elevated until after the first wave of mitosis at 28-30 hours.…”
Section: Intraperitoneal Injection Of 20-methylcholanthrenesupporting
confidence: 92%
“…It may be relevant that thioacetamide has the property of breaking dormancy of tubers, and it was suggested that thiol compounds may inactivate the growth-inhibitory unsaturated ketonic substances by addition reactions (Sexton, 1949). The amount of acid-soluble thiol compounds increases during the late pre-replicative period of liver regeneration in the rat (Fraser & Cater, 1967).…”
Section: Adolescent Ratsmentioning
confidence: 98%